A Perfect Storm in the Amazon Wilderness Success and Failure in the Fight to Save an Ecosystem of Critical Importance to the Planet - Killeen, Timothy J. (The White Horse Press, 2021)
Vital reading for all those interested in the conservation of the world's most important ecosystem. In a lucid style backed by encyclopaedic knowledge, Killeen unpicks the extremely complex ecological and socio-political threads that comprise the recent history and the vital future of the Pan Amazon region. The fight to save the Amazon is a fight for sustainability that is emblematic of the entire future of human co-existence with Nature on Earth. Killeen is an authoritative and impassioned guide, eschewing soundbites in favour of a clearsighted and highly nuanced picture of the realities on the ground. Only in understanding present realities and how they came to pass, he argues, can we proceed hopefully into the future. Events of the last ten years are discussed in detail, because future events will have to build upon - or modify - the cultural and economic forces driving events in the Pan Amazon. Nonetheless, the text provides a longer historical perspective to show how policies create legacies that reverberate over decades, long after they have been recognised as being fundamentally flawed.